Downregulated Expression of hsa_circ_0005556 in Gastric Cancer and Its Clinical Significance. (19th November 2019) - Yang, Liangwei; Yu, Yu; Yu, Xiuchong; Zhou, Jiaming; Zhang, Zhiping; Ying, Shibo; Guo, Junming; Yan, Zhilong
Abstract : Background . Gastric cancer (GC) has a poor prognosis due to the lack of ideal tumor markers. Circular RNAs (circRNAs) are a novel type of noncoding RNA related to the occurrence of GC. Among our research, we investigated the role of hsa_circ_0005556 in GC. Materials and Methods . The expression of hsa_circ_0005556 of 100 paired GC tissues and adjacent normal tissues was detected using quantitative reverse transcription-polymerase chain reaction (qRT-PCR). A receiver operating characteristic (ROC) curve was established to evaluate the diagnostic value of hsa_circ_0005556. The correlation between the expression of hsa_circ_0005556 and corresponding clinicopathological characteristic was explored. Results . hsa_circ_0005556 was significantly downregulated in GC tissues contrasted with adjacent normal tissues (n = 100, p < 0.001 ). The areas under the ROC curve (AUC) of hsa_circ_0005556 were up to 0.773, while 64% sensitivity and 82% specificity, respectively. Moreover, its expression levels were significantly associated with differentiation (p = 0.001 ), TNM stage (p = 0.013 ), and lymphatic metastasis (p = 0.039 ). GC patients of high hsa_circ_0005556 levels had a longer overall survival (OS) than those of the low group (p = 0.047 ). Conclusion . hsa_circ_0005556 is a potential biomarker for GC, which may guide judgment of the indication of endoscopic treatment for early gastric cancer (EGC).